High Prevalence of Obesity in a Saudi Community K.Aljabri, MD, FRCPC, S. Bokhari, MD. A Cross Section, Single Centre Study - Khalid S. Aljabri; Samia A. Bokhari (Journal of Obesity Management, 2014)
Objective: Obesity is a major public health problem worldwide. We designed this study to determine the prevalence of obesity among Saudis in the department of primary care at King Fahad Armed Forces Hospital. Methods: Cross section study of Saudis of both sexes, aged more than or equal to 12 years at the department of primary care at King Fahad Armed Forces Hospital between January 2008 and June 2009. Results: A total of 5968 were attending the department of primary care were included in this study. There were 2269 (38.0%) male and 3699 (62.0%) female. With age, a gradual increase was seen in the Body mass index (BMI) in both males and females, up to the age of 59 years, with a decrease occurring thereafter. In the females below 20 years of age, the BMI was lower than in the male group. Above 30 years, the BMI in females was higher than in the males of corresponding ages. The prevalence of BMI≥25 was 70.0%.The prevalence of BMI≥25 was non significantly higher in the male compared to the female,71% and 69.3% respectively, p=0.2.The prevalence of overweight ( BMI=25-29.9) was higher in the males compared to the females, while the reverse was true for obesity(≥30),where 62.0% of the total female population was obese compared to 49.7% of the total male population. The magnitude of the difference in prevalence of obesity in the males and females was significantly high ( p<0.0001). Conclusion: The prevalence of obesity is high among Saudi population at the primary care setting and represents a major clinical and might represent a public health problem. A national prevention program at community level should be implemented.
Keywords: Obesity